Long-Term Fate of Human Fetal Liver Progenitor Cells Transplanted in Injured Mouse Livers. (13th October 2017) - Irudayaswamy, Antony; Muthiah, Mark; Zhou, Lei; Hung, Hau; Jumat, Nur Halisah Bte; Haque, Jamil; Teoh, Narcissus; Farrell, Geoffrey; Riehle, Kimberly J.; Lin, Jaymie Siqi; Su, Lin Lin; Chan, Jerry Ky; et al.
Abstract : Liver progenitor cells have the potential to repair and regenerate a diseased liver. The success of any translational efforts, however, hinges on thorough understanding of the fate of these cells after transplant, especially in terms of long-term safety and efficacy. Here, we report transplantation of a liver progenitor population isolated from human fetal livers into immune-permissive mice with follow-up up to 36 weeks after transplant. We found that human progenitor cells engraft and differentiate into functional human hepatocytes in the mouse, producing albumin, alpha-1-antitrypsin, and glycogen. They create tight junctions with mouse hepatocytes, with no evidence of cell fusion. Interestingly, they also differentiate into functional endothelial cell and bile duct cells. Transplantation of progenitor cells abrogated carbon tetrachloride-induced fibrosis in recipient mice, with downregulation of procollagen and anti-smooth muscle actin. Paradoxically, the degree of engraftment of human hepatocytes correlated negatively with the anti-fibrotic effect. Progenitor cell expansion was most prominent in cirrhotic animals, and correlated with transcript levels of pro-fibrotic genes. Animals that had resolution of fibrosis had quiescent native progenitor cells in their livers. No evidence of neoplasia was observed, even up to 9 months after transplantation. Human fetal liver progenitor cells successfully attenuate liver fibrosis in mice. They are activated in the setting of liver injury, but become quiescent when injury resolves, mimicking the behavior of de novo progenitor cells. Our data suggest that liver progenitor cells transplanted into injured livers maintain a functional role in the repair and regeneration of the liver. Abstract : Human hepatocytes engrafting in mouse liver 4 weeks after transplantation illustrated with immunofluorescence of human- and mouse-specific Zona occludens-1 (ZO-1) antibodies. Human-specific ZO-1 (green) colocalize with mouse ZO-1 (red) showing yellow canaliculi junctions where human and neighboring mouse cells have integrated within the liver cords. ×80 magnification.